A review of charging infrastructure layout planning and electric vehicle traffic simulation application. Issue 1 (July 2021) - Hu, Susanna; Mao, Feng; Chen, Jinhua; Li, Zhiheng
Abstract: As environmental pollution and energy constraints, especially oil supply, become more prominent, electric vehicles (EVs), being more environmentally friendly than conventional vehicles, is an effective way to help alleviate the environmental problems. However, the range anxiety caused by limited battery capacity has led many potential consumers to become distrustful towards electric vehicles. In addition, the demand for charging increases with the rise in EV ownership, which stresses the importance of the large-scale deployment of charging infrastructure, and a reasonable layout of charging facilities. This paper first summarizes the travel behavior of electric vehicles, followed by reviewing different models and methods of charging infrastructure layout planning, and finally outlines the research application of electric vehicle traffic simulation and provides an outlook on the problems to be improved. For instances, lacking data volume in current researches on electric vehicle travel behavior; charging infrastructure layout planning are often limited to the framework of traditional layout research; traffic simulations fail to consider the characteristics of electric vehicles are some discussed problems. Hence, future researches should integrate new technologies such as artificial intelligence and cloud computing to improve the above issues.